MENSAGEM DOS DIRIGENTES - Friede, Reis; Azulay Neto, Messod; Oliveira Júnior, Osair Victor de (Revista da Seção Judiciária do Rio de Janeiro - Auditorium; v. 24 n. 49 (2020): II Seminário de Direitos Humanos: em tempos de Pandemia, 2020)
MENSAGEM DOS DIRIGENTES